Mandates and Implementation of Child Rights by Local Governments in Nepal - Vaidya, Rashesh; Baniya, Bam Bahadur (Journal of Nepalese Studies, 2025)
This paper examines the status and practices of child-friendly local governance in Nepal, with a focus on selected wards of Kathmandu Metropolitan City. A descriptive research design was adopted. Primary data were collected through structured interviews and focus group discussions with 25 respondents from five wards, using non-probability quota sampling, and were supplemented by secondary data from legal and policy documents. The findings reveal low public awareness of constitutional and legal mandates on child rights at the local level. While basic services such as birth registration and vaccination are generally accessible, broader child rights initiatives are inconsistently implemented and often perceived as symbolic. Political prioritization of revenue-generating sectors, weak institutional commitment, and limited cultural relevance constrain the effective realization of child-friendly local governance.